2014
DOI: 10.1097/mlr.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Potentially Avoidable Hospitalizations

Abstract: Our analyses demonstrate that administrative data can be effective in predicting ACSC hospitalizations. With high predictive ability, the model can assist primary care providers to identify high-risk patients for early intervention to reduce ACSC hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 32 publications
0
65
1
2
Order By: Relevance
“…The majority of models (18 of 27) were developed to predict emergency hospital admission at 12-month follow-up (range, 90 d–4 y). Of these, 3 models focused on emergency admissions for chronic disease or conditions amenable to primary care management as a primary outcome measure 27,31,38. Two models predicted any hospitalization and 2 predicted occupied bed days over specific time periods 17,26,32,38.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of models (18 of 27) were developed to predict emergency hospital admission at 12-month follow-up (range, 90 d–4 y). Of these, 3 models focused on emergency admissions for chronic disease or conditions amenable to primary care management as a primary outcome measure 27,31,38. Two models predicted any hospitalization and 2 predicted occupied bed days over specific time periods 17,26,32,38.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies presented their final risk model only and not all variables considered for inclusion, and 1 study uses locally available data to create a risk prediction model specifically for a named population so variables considered for inclusion vary 23–25,27,28,31,34,37. The most frequently included predictor variables in final risk models were: (1) named medical diagnoses (23 models); (2) age (23 models); (3) prior emergency admission (22 models); and (4) sex (18 models).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…67 Most models, until more recently, did not include mental health data. A recent systematic review of risk prediction models to predict EHA in community-dwelling adults identified 27 unique risk prediction models, 349 of which only 12 included data on mental illness, 67,[350][351][352][353][354][355][356][357][358] three included data on living alone 356,359,360 and none included data about threatening life events. Of the 12 models that included data on mental illness, all were published during the lifetime of this programme.…”
Section: Relevance Of Programme Findings For Risk Modellingmentioning
confidence: 99%